2021
DOI: 10.1038/s41598-021-89625-2
|View full text |Cite
|
Sign up to set email alerts
|

IL-23 receptor deficiency results in lower bone mass via indirect regulation of bone formation

Abstract: The IL-23 receptor (IL-23R) signaling pathway has pleiotropic effects on the differentiation of osteoclasts and osteoblasts, since it can inhibit or stimulate these processes via different pathways. However, the potential role of this pathway in the regulation of bone homeostasis remains elusive. Therefore, we studied the role of IL-23R signaling in physiological bone remodeling using IL-23R deficient mice. Using µCT, we demonstrate that 7-week-old IL-23R−/− mice have similar bone mass as age matched littermat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Razawy et al showed that 7-week-old IL-23R-/-mice have a bone mass similar to age-matched littermate control mice. In contrast, 12-week-old IL-23R-/-mice have signi cantly lower trabecular and cortical bone mass, shorter femurs, and more fragile bones [35]. Our results suggest a relationship between in ammation, alterations in the IL-23R, and the etiology of LCPD.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Razawy et al showed that 7-week-old IL-23R-/-mice have a bone mass similar to age-matched littermate control mice. In contrast, 12-week-old IL-23R-/-mice have signi cantly lower trabecular and cortical bone mass, shorter femurs, and more fragile bones [35]. Our results suggest a relationship between in ammation, alterations in the IL-23R, and the etiology of LCPD.…”
Section: Discussionmentioning
confidence: 59%
“…The IL-23R signal translation pathway has been extensively studied for its relationship with proin ammatory diseases and different pathologies that cause bone deterioration. In addition, the signaling pathway that occurs after the activity of IL-23R has plethoric effects on osteoblast and osteoclast differentiation since it can inhibit or stimulate both processes [35]. Razawy et al showed that 7-week-old IL-23R-/-mice have a bone mass similar to age-matched littermate control mice.…”
Section: Discussionmentioning
confidence: 99%
“…Altered expression of DLK1 [62], DBH (dopamine beta-hydroxylase) [63] and CYP17A1 [64] have previously been shown to promote depression and anxiety. DLK1 [65] and IL23R [66] were shown to participate in facilitating the osteoporosis. DBH (dopamine beta-hydroxylase) [67] has been reported to enhance CF development.…”
Section: Discussionmentioning
confidence: 99%
“…Increased expression of IL-22 leads to the new periosteal bone formation through ignal transducer and activator of transcription 3 (STAT3) activation and increased expression of genes that regulate the bone formation, including the Wnt family members. In vitro studies, IL-23R-/-mice had lower cortical bone mass related to indirect effects of IL-23R on osteoblasts [9]. Also, IL-23 can reduce osteoclastogenesis via the induction of granulocytemacrophage colony-stimulating factor (GM-CSF) in murine T cells, which can reduce osteoclast formation [10].…”
Section: Early Onlinementioning
confidence: 99%